Thrombectomy for a Patient with Concomitant Acute Cervical Internal Carotid and Middle Cerebral Artery Occlusion: Video Case. (July 2019) - Tian, Fucheng; Abi‐Aad, Karl R; Bendok, Bernard R; Krishna, Chandan
Abstract : Abstract : We present the case of a 62‐yr‐old female who presented with ground‐level fall and new onset of left‐sided weakness of 30 min duration. CT angiogram revealed right ICA pseudo‐occlusion and thrombus filling the right proximal M1 segment of the right MCA. On detailed neurological exam patient was noted to have NIHSS of 25. Patient was started on IV TPA infusion and was taken to interventional angiography suite after an informed consent was obtained. Diagnostic angiography was performed which demonstrated critical stenosis of the right proximal internal carotid artery. Right carotid artery stenting and balloon angioplasty of the carotid stent with distal embolic protection device was performed. Post carotid stent angiogram once again confirmed proximal right M1 pseudo‐occlusion in the right MCA distribution. The clot was removed using a stent retriever, thus achieving complete recanalization (TICI 3) of the right cerebral hemisphere. The patient returned to baseline neurological status and a 1 mo follow‐up diagnostic angiogram revealed patent carotid stent. Following the case presentation, we present the nuances of acute ischemic stroke management of large vessel occlusion with an emphasis on technical nuances, recent published guidelines1 and the literature.2-8